Water harvesting: Reviving ancient techniques - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The recent recurrent droughts and famine in parts of Africa have revived iriterest in an ancient technology, that of water harvesting. This system of water conservation, involving the collection and storage of run-off from infrequent storms and...